Cystic Artery Control with Bipolar Electrocauterization During Laparoscopic Cholecystectomy - Iqbal, Sajid; Tabassum, Saima (Lietuvos chirurgija, 2023)
Laparoscopic cholecystectomy is a widely practiced procedure for symptomatic cholelithiasis. Haemostasis of cystic artery can be achieved with clips electrocautery and ultra modern vessel sealing energy devices. Bipolar electro coagulation of cystic artery is safe and a cost effective measure in developing countries. Our aim was to establish the feasibility of bipolar electrocautery in securing cystic artery. We conducted a prospective study on 120 patients in different age and sex groups. Correctable co morbidities were not a contraindication to inclusion criteria. Anatomical variations in size, origin and number of cystic artery were noted.